Voicing Beliefs on Global Leadership for Dentistry - Hermina Harnagea; Christophe Bedos; Ryma Kabir; Aimée Dawson; France Power; Anita Brown-Johnson; Elham Emami (Elsevier, 2022)
ABSTRACT: Background: Dental leadership in different models of care is not well documented, and therefore the objectives of this study were to explore how dental leaders develop their own leadership and how they engage others to increase access to oral health services as well as to describe perceived challenges in developing coalitions for promoting oral health care. Methods: We adopted a qualitative descriptive research methodology. We recruited dental leaders using a purposeful sampling approach and a snowball technique. Data were collected using a remote digital platform; we organised semi-structured interviews based on the LEADS conceptual framework. Saturation was reached after 11 interviews. Data analysis included the following iterative steps: decontextualisation, recontextualisation, categorisation, and data compilation. The analysis was performed manually, assisted by the use of QDA Miner software. Results: Fourteen dental leaders participated in the study. Our analysis revealed 3 overarching themes: (I) lead self, with 3 subthemes: leadership insights; leadership traits; opportunity-role model dyad; (II) leadership strategies; and (III) challenges in leadership development, with 3 subthemes: limited engaged practice and workforce, valorise the image of dentistry, and lack of leadership training. Conclusions: Our research findings showed that, despite a limited scope of leadership in dentistry, the dental leaders recognise its importance and acknowledge the need for formal training and mentorship at different levels. This study identified challenges in dental leadership development that could further orient dental education programmes and support the implementation of evidence-based, high-quality, and efficient oral health services.